A Contribuição de José Saturnino da Costa Pereira para o Cálculo das Variações - Magalhães, Cláudio Márcio Ribeiro (2006)
In this work we present, a brief story on the history of the Calculus of the Variations, as well as, some of the mathematicians who had directly contributed so that he had the development, of that are an area of the widely studied Mathematics since its sprouting. We also present, the context of the time where this subject was developed in Brazil, as well as the first known publication. In annex we are available the work of the mathematician José Saturnino da Costa Pereira, published in the magazine the Patriot in the year of 1813, we detach the importance of the same in the development of Science in Brazil